Treatment of corneal astigmatism by limbal relaxing incisions during phacoemulsification surgery - Maged A Naguib; Hussam E.O Elrashidy; Ghada Samir (Wolters Kluwer Medknow Publications, 2022)
Background and aim The aim was to assess the effectiveness of limbal relaxing incisions (LRIs) in treatment of astigmatism in patients undergoing phacoemulsification surgeries. Patients and methods Forty-eight eyes of 48 patients suffering from senile cataracts of mean age 64.7±7.9 (range: 50-77) years, and mean corneal astigmatism 1.8±0.73 diopters (D) (range: 1.5-3.5 D) were included in this study. All LRIs were performed at the end of phacoemulsification. Corneal topography results were compared before surgeries and 2 and 6 months after surgeries. Results A statistically significant reduction in the mean corneal astigmatism was seen from 1.8±0.73 D (range: 1.50-3.50) preoperatively to 1.1±0.24 D (range: 0.5-1.7) and 1.4±0.52 D (range: 0.60-1.9) in the second and sixth postoperative months, respectively (P<0.001). Surgical-induced astigmatism (the amount and axis of astigmatism change induced by surgery) was 0.90±0.48 at 2 months and 0.96±0.59 at 6 months. Correction index (calculated by determining the ratio of surgical-induced astigmatism/target-induced astigmatism) was 0.56±0.42 and 0.57±0.33 at 2 and 6 months, respectively. Index of success (ratio of topographic residual astigmatism and target-induced astigmatism) was measured to be 0.45±0.42 and 0.48±0.33 at months 2 and 6 correspondingly. Conclusion Combined LRI and phacoemulsification appears to be safe and fairly effective to correct mild-to-moderate corneal astigmatism. However, undercorrection is a common limitation that may be further managed by modified nomograms in future studies.